THE APPLICATION OF SILVOFISHERY ON TILAPIA (Oreochromis niloticus) AND MILKFISH (Chanos chanos) FATTENING WITHIN MANGROVE ECOSYSTEM OF THE NORTHERN COASTAL AREA OF SEMARANG CITY - Rini Budihastuti; Sutrisno Anggoro; Suradi W. Saputra (JOURNAL OF COASTAL DEVELOPMENT, 2012)
The most influencing area on the preservation of the coastal environment is mangrove forest. Mangrove ecosystem is interface between land and sea ecosystem, thus this ecosystem possesses specific function in that its continuity depends on dynamics occurred in the land and sea ecosystem. Mangrove ecosystem is one of several ecosystems in that it has high productivity that produces food resource for most of shore biota. Besides, from fishery side, mangrove also possesses role as spawning and nursery grounds. Nevertheless, the condition of mangrove in Indonesia is experiencing damage and width shortening. To hold the degradation speed of mangrove forest, one appropriate effort could be silvofishery. Silvofishery in an integrated activity between brackish water fishery and mangrove forest cultivation at the same location. The research was completed in northern coastal area of Mangunharjo Sub-district, Tugu district, Semarang City. The purpose of the research was to review the most appropriate mangrove type and appropriate cultivated species for silvofishery for maximized result. The method of research action was completed upon multivariate experiment, consisted of 2 factors, which were mangrove vegetation (Avicenia marina and Rhizopora mucronata) and 2 types of cultivated species of tilapia (Orechromis niloticus) and milkfish (Chanos chanos) and with 2 times repetition. Based upon the data obtained, it can be concluded to develop optimal silvofishery were R. mucronata with milkfish cultivated species and A. marina with tilapia cultivated one.